2015
DOI: 10.1104/pp.114.256578
|View full text |Cite
|
Sign up to set email alerts
|

Histone H2B Monoubiquitination Mediated by HISTONE MONOUBIQUITINATION1 and HISTONE MONOUBIQUITINATION2 Is Involved in Anther Development by Regulating Tapetum Degradation-Related Genes in Rice  

Abstract: Histone H2B monoubiquitination (H2Bub1) is an important regulatory mechanism in eukaryotic gene transcription and is essential for normal plant development. However, the function of H2Bub1 in reproductive development remains elusive. Here, we report rice (Oryza sativa) HISTONE MONOUBIQUITINATION1 (OsHUB1) and OsHUB2, the homologs of Arabidopsis (Arabidopsis thaliana) HUB1 and HUB2 proteins, which function as E3 ligases in H2Bub1, are involved in late anther development in rice. oshub mutants exhibit abnormal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 90 publications
(125 reference statements)
9
44
0
Order By: Relevance
“…H2Bub1 plays critical roles in regulating growth and development (Fleury et al ; Liu et al ; Cao et al ; Gu et al ; Schmitz et al ; Xu et al ; Bourbousse et al ; Himanen et al ; Cao et al ), as well as in modulating defence or immune responses and in cuticle composition in plants (Devoto et al ; Dhawan et al ; Hu et al ; Menard et al ; Zou et al ). In the present study, we demonstrated that H2Bub1 played an important role in response to salt stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H2Bub1 plays critical roles in regulating growth and development (Fleury et al ; Liu et al ; Cao et al ; Gu et al ; Schmitz et al ; Xu et al ; Bourbousse et al ; Himanen et al ; Cao et al ), as well as in modulating defence or immune responses and in cuticle composition in plants (Devoto et al ; Dhawan et al ; Hu et al ; Menard et al ; Zou et al ). In the present study, we demonstrated that H2Bub1 played an important role in response to salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…hub1 and hub2 mutants show the loss of H2Bub1 (Liu et al 2007;Cao et al 2008;Bourbousse et al 2012;Himanen et al 2012;Zou et al 2014). Multiple developmental processes and responses to biotic stress have been suggested to be closely related to H2Bub1 in plants, such as seed dormancy and leaf and root growth (Fleury et al 2007;Liu et al 2007), control of flowering time and plant development (Cao et al 2008;Gu et al 2009;Schmitz et al 2009;Xu et al 2009;Cao et al 2015), photomorphogenesis and the circadian clock (Bourbousse et al 2012;Himanen et al 2012), and defence or immune responses and cuticle composition (Dhawan et al 2009;Menard et al 2014;Zou et al 2014). Moreover, we previously demonstrated that H2Bub1 was involved in modulating microtubule (MT) disassembly during biotic stress (Hu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, reduced acetylation might be implicated in the cytological changes of aleurone cell death. DNA methylation and histone monoubiquitination have been shown to play an important role in regulating PCD in tapetum (Solís et al, 2014;Cao et al, 2015).…”
Section: Discussion Hdacs Are Necessary For Inducing the Ga-initiatedmentioning
confidence: 99%
“…Characterization of the hub1, hub2, hub1hub2 and ubc1ubc2 mutants has revealed that H2Bub1 regulates multiple processes, including cell cycle and plant growth (Fleury et al, 2007;Lolas et al, 2010), seed dormancy (Liu et al, 2007), leaf cuticle formation (M enard et al, 2014), flowering (Cao et al, 2008;Gu et al, 2009;Xu et al, 2009), circadian clock and photomorphogenesis (Bourbousse et al, 2012;Himanen et al, 2012), as well as plant defense (Dhawan et al, 2009;Zou et al, 2014). More recent studies have demonstrated that knockdown of HUB1/HUB2 in tomato also affects plant response to pathogens (Zhang et al, 2015) and loss of HUB1/HUB2 in rice leads to early heading, dwarfism and anther developmental defects (Cao et al, 2015). Impaired deposition of H3K4me3 or H3K36me3 also affects a range of plant growth and developmental processes (for a recent review, see Fletcher, 2017).…”
Section: Introductionmentioning
confidence: 99%